Alcohol purchases from a large Finnish retail chain before and after a change in alcohol legislation. (30th September 2020) - Uusitalo, L; Nevalainen, J; Rahkonen, O; Erkkola, M; Saarijärvi, H; Fogelholm, M; Lintonen, T
Abstract: Background: In January 2018, the legal limit for alcoholic beverages in grocery stores changed from 4.7 to 5.5 % alcohol. The increased availability of stronger beer, cider and ready-to-drink beverages was expected to increase the total amount of 100% alcohol bought. The study aimed to examine how the change in alcohol legislation affected the purchasing of 100% alcohol from grocery stores by comparing the years 2017 and 2018. Methods: The study data consisted of 47, 066 loyalty card holders of Finland's largest retail chain, who gave their consent and provided background information by an online questionnaire. The data contained the type, volume and alcoholic content of the purchases, from which we calculated the amount of 100% alcohol bought. The mean individual alcohol purchases in the years 2017 and 2018 were compared by age, gender, level of education and household income using repeated measurements ANOVA models. Results: There was only a small, non-significant change in the total amount of 100% alcohol between 2017 and 2018 (mean 1.9 l and 2.0 l, respectively, p = 0.220). Lower income was associated with a decrease in total 100% alcohol purchased, whereas higher income groups showed an increase. Increase in 100% alcohol bought as ready-to-drink beverages was seen in all population groups. Conclusions: The availability of stronger alcoholic beverages in grocery stores did not result in a notable overall increase in total purchases of 100% alcohol. The increased purchases of alcohol as ready-to-drink beverages were, on the average, compensated for by decreased purchases of alcohol as other beverages. The association of income with total alcohol purchases may indicate the effect of price in consumer behavior. Key messages: The raise in the legal limit of alcohol content raised did not result in a significant increase in the total amount of 100% alcohol bought from grocery stores. Alcohol purchased as ready-to-drink beverages increased in all population groups.